Current Caribbean bibliography. - Bibliographie courante de La Caraibe. - Bibliografia corriente del Caribe. 1965. Vol. 15. Comp. and ed. by Luisa C. Vigo-Cepeda. [...] (Caribbean Economic Development Corporation, 1968)
Index.